Does nutrition have an effect on the timing of tooth formation?. Issue 3 (20th December 2019) - Esan, Temitope A.; Schepartz, Lynne A.
Abstract: Background: The effect of nutritional status on the timing of permanent tooth formation is not well understood, despite clear evidence that systemic stresses result in enamel defects during tooth formation. Aim: This study investigated the effect of nutritional status (measured as BMI, height, weight, mid‐upper arm circumference, and head circumference) on permanent tooth formation. Method: This was a prospective cross‐sectional study involving 642 (270 males, 372 females) healthy Black South African participants aged 5–20 years. The height and BMI were converted to z‐scores using WHO z‐score for age tables. The participants were grouped into underweight/short for age (<−2), normal (≥ − 2 to 2.0) and overweight/obese/tall for age (>2). Panoramic radiographs of the children were assessed using Demirjian's eight stages of permanent tooth formation and age was estimated using Demirjian's method. Probit regression analysis was used to calculate the mean age of attainment of the developmental stages for the left mandibular teeth (I2–M2). Results: There was significant advancement in the age of attainment of the final (H) stage for the majority of permanent teeth in the overweight (mean male BMI 22.9; female 27.94) group compared to the underweight ( p  < .05). Negative binomial regression indicated that age, height, and BMI were significant predictors of the dental maturity score for males ( p  < .05), while age, height, weight, BMI and HC were significant predictors for females ( p  < .05). Conclusion: Nutritional status had a significant effect on the timing of tooth formation in males and females in the study population. The effect was mainly noticeable for children in the extremes of the spectrum of BMI z‐scores.